The Islamic revival in Kazakhstan in the 90s of the 20 century - Mustafayeva, А. А. (Journal of Oriental Studies, 2016)
The paper shows the Islamic revival during the first years of Kazakhstan’s independence as an external factor such as building-up diplomatic relations with the Islamic world as well as an internal factor such as the filling vacuum caused by the soviet ideology.